UNIFICATION OF EDUCATIONAL AND PEDAGOGICAL FORECASTING IN THE UKRAINIAN SOCIALIST SOVIET REPUBLIC OF THE PERIOD 1930-1940 - Cherniak S. G. (International Journal of Innovative Technologies in Social Science, 2023)
The article is devoted to the problem of the unification of educational and pedagogical forecasting in the Ukrainian Socialist Soviet Republic of the period 1930-1940. The author emphasizes that the unification of educational and pedagogical forecasting in the Ukrainian Soviet Socialist Republic of the period 1930-1940 hid the threat of a social explosion, led to the strengthening of the national course to build a communist society. All this affected the invariant component of the content of educational and pedagogical forecasting in the context of dominant socio-economic (industrialization, collectivization) and political (monopolization, curtailment of Ukrainization) factors. During the studied period, we focus on the spread of state institutions of higher pedagogical education, in particular, industrial-pedagogical institutes, institutes of social education, pedagogical technical schools, which determined new conditions for staffing higher schools. We also emphasize the search for the optimal model of the functioning of the education system and the development of numerous teacher training projects.